History review of the development and use of psychological tests in Croatia - Matešić, Krunoslav (2001)
In the Republic of Croatia, systematic testing has been organised since 1931, when the Vocational Guidance Center was established. Translations and adaptations of some foreign tests were used in the beginning, but from the mid 1930's, instruments constructed by Academician Zoran Bujas (born 1910) were introduced. The Bujas Z-series and R-series, published prior to World War II, served as the basis for the creation of the M-series and B-series tests in the 1950's. Bujas, as the leading psychologist in Croatia, until his retirement in 1980, has constructed around 40 different tests with his co-workers, some of which were accepted in applied psychology. Since the beginning the the sixties in the former Yugoslavia, and thereby also in Croatia, adaptations of American tests were introduced for the area of ability measurements, while various personality questionnaires by leading world authors are introduced for practical use. With the independence of Croatia (1992) a gap remained in this area, which was gradually filled by newly formed, mainly private, publishers. In the EFPPA questionnaire conducted in 1999, Croatian psychologists stated that they use about 60 tests in their work. The introduction of new tests is slow, as work on them is classified as professional, not scientific, which is legally required for professional advancement. However, it is very positive that tests of ability and personaltiy are conducted exclusively by psychologists. Possible interpretations or findings of other professionals are not legally founded.
Pregledni rad.
ENG